Correlation Between the Meanings of the Core Lexemes of the Russian Concepts of Holiday and Everyday Life (Based on Advertising Media Discourse) - Olga P. Kasymova; Anna S. Leonova (Вестник Северного (Арктического) федерального университета: Серия «Гуманитарные и социальные науки»)
The purpose of this article is a systematic description of the core lexemes of the Russian concepts of prazdnik (‘holiday’) and budni (‘everyday life’) based on the material of advertising microtexts that have not been previously studied in this aspect. A comparative linguistic analysis of the meaning and functioning of these core lexemes allowed us to identify common and specific features in their semantic structure. Texts of modern media advertisements that incorporate the concepts in question were chosen as the object of this research, while core lexemes (excluding the periphery, i.e. synonyms, phraseological units and associations), as the subject. The material was selected from regional advertisements and videos of recent years using the continuous sampling method. When working with the materials, the authors applied the methods of component, correlation, and contextual analysis, as well as the corpus method. The general function of the concepts under study in the analysed texts is to promote goods and services. The word prazdnik means a non-working day as well as a happy, joyous day on which important, pleasant events take place. The word budni carries the opposite meaning, i.e. monotonous, dull everyday life. In the context of advertising, the word prazdnik has an additional sense: a product that is purchased or organized; discounts are called prazdnik, as well as various important events in life. The word budni, on the contrary, has not developed any additional meanings; it is less functional compared to the word prazdnik and acts as a trigger designed to evoke associations opposite to prazdnik in order to emphasize the contrast between budni and prazdnik and its synonyms.